If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + 2(y + -5) = 5(y + 2) + -4 Reorder the terms: 7y + 2(-5 + y) = 5(y + 2) + -4 7y + (-5 * 2 + y * 2) = 5(y + 2) + -4 7y + (-10 + 2y) = 5(y + 2) + -4 Reorder the terms: -10 + 7y + 2y = 5(y + 2) + -4 Combine like terms: 7y + 2y = 9y -10 + 9y = 5(y + 2) + -4 Reorder the terms: -10 + 9y = 5(2 + y) + -4 -10 + 9y = (2 * 5 + y * 5) + -4 -10 + 9y = (10 + 5y) + -4 Reorder the terms: -10 + 9y = 10 + -4 + 5y Combine like terms: 10 + -4 = 6 -10 + 9y = 6 + 5y Solving -10 + 9y = 6 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -10 + 9y + -5y = 6 + 5y + -5y Combine like terms: 9y + -5y = 4y -10 + 4y = 6 + 5y + -5y Combine like terms: 5y + -5y = 0 -10 + 4y = 6 + 0 -10 + 4y = 6 Add '10' to each side of the equation. -10 + 10 + 4y = 6 + 10 Combine like terms: -10 + 10 = 0 0 + 4y = 6 + 10 4y = 6 + 10 Combine like terms: 6 + 10 = 16 4y = 16 Divide each side by '4'. y = 4 Simplifying y = 4
| 2x-5(8-x)=9 | | In(1-2y)=t | | 68=5x-18 | | (3x-7)+3=2x+14 | | 11-(9y+5)=-9 | | 4(x+7)+6=9x-5(x-4) | | 5x-18=68 | | x^3+X^2-5x-125=0 | | In(y-40)=5t | | 3/2/6/4=18/n | | 3/2/6/4=18n | | 5t-11=-13+4t | | Iny=-t+5 | | 5n-3=-1+3n | | -2(5s-3)-6=-3(7s+3)-3 | | log(5-3x)=2 | | -12x+2=20x | | 4x-8+2x=5(3x+2) | | 29+3y-10=13y-13-2y | | Iny=2t+4 | | 4(a+2)-17=15 | | -7p+5+8p=8 | | 10(v+1)-2v=4(2v+4)-17 | | -35=4x-10 | | 220=2.5(50)+b | | (3-w)(3w-1)=0 | | 3-5(n-4)=16 | | 3x+17=22 | | -0.3x+9.13=-0.1x+9.53 | | (2ab+2ab+2ab+2ab+2ab)+(7ab+7ab)+(5ab+5ab)+1ab= | | 3m=5-2m | | cosx=0.4166666667 |